Pengendalian Persediaan Sparepart Area Gudang Menggunakan Metode Continuous Review System (CRS) pada PT Indotruck Utama - Mulyadi, Agus; Meirizha, St Nova; Yul, Faradila Ananda; Permata, Dear Rani (SURYA TEKNIKA, 2025)
PT Indotruck Utama is a company that supplies and distributes heavy equipment, including Volvo trucks and construction equipment. One of the main problems this company faces is overstocking in the warehouse, which can lead to additional storage space, increased inventory costs, and the risk of damage to goods. This research aims to optimize inventory management by controlling stock at an ideal level and comparing the current total inventory cost with the proposed price. In this study, the Continuous Review System method is applied by first grouping spare parts using the ABC method. This method categorizes inventory items based on the contribution of fund absorption, where category A items absorb the most significant funds, category B is intermediate, and category C has the most minor fund absorption. A total of 24 spare parts items were grouped into these three categories. Next, inventory requirements were forecasted using historical data to estimate the number of spare parts required in the future. Based on the forecasting results, estimated inventory requirements, optimal ordering point (Q*), reorder point, and safety stock were calculated for each item. The results showed that the current total inventory cost reached Rp 343,368,047.63, while with the implementation of the Continuous Review System, the cost can be reduced to Rp 333,425,336.79. Thus, there is a savings of Rp 9,942,710.84 or about 2.90%.